Given #y = e^((ln x)^2)# how do you find find y'(e)?

Answer 1
Recall that #d/dxe^x=e^x#. Then, through the chain rule, #d/dxe^f(x)=e^f(x)f'(x)#.

So:

#y(x)=e^((lnx)^2)#
#y'(x)=e^((lnx)^2)d/dx(lnx)^2#
#color(white)(y'(x))=e^((lnx)^2)(2(lnx))d/dxlnx#
#color(white)(y'(x))=(2e^((lnx)^2)lnx)/x#

Then:

#y'(e)=(2e^((lne)^2)lne)/e#
#color(white)(y'(e))=(2e^1(1))/e#
#color(white)(y'(e))=2#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

# dy/dx = (2e^(ln^2x)lnx)/x => y'(e) = 2#

We have:

# y = e^(ln^2x) #

Take Natural Logarithms of both sides:

# ln y = (lnx)^2 #

Differentiate Implicitly, and apply the chain rule:

# 1/y * dy/dx = 2(lnx)*(1/x) #

Which we can rearrange to get:

# dy/dx = (2ylnx)/x # # " " = (2e^(ln^2x)lnx)/x #
So then, when #x=e# we have:
# dy/dx = (2e^(ln^2e)lne)/e # # " " = (2e^1*1)/e # # " " = 2 #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find ( y'(\text{e}) ) for the function ( y = e^{(\ln x)^2} ), you'll need to use the chain rule.

Given that ( y = e^{(\ln x)^2} ), take the derivative of ( y ) with respect to ( x ), and then evaluate it at ( x = \text{e} ).

Here's the process:

  1. Find ( y' ) using the chain rule: [ y' = \frac{d}{dx} \left( e^{(\ln x)^2} \right) = e^{(\ln x)^2} \cdot 2(\ln x) \cdot \frac{1}{x} ]

  2. Substitute ( x = \text{e} ) into ( y' ): [ y'(\text{e}) = e^{(\ln \text{e})^2} \cdot 2(\ln \text{e}) \cdot \frac{1}{\text{e}} ]

  3. Simplify: [ y'(\text{e}) = e^{(\ln \text{e})^2} \cdot 2 \cdot \frac{1}{\text{e}} ]

  4. Remember that ( \ln \text{e} = 1 ): [ y'(\text{e}) = e^{1^2} \cdot 2 \cdot \frac{1}{\text{e}} ]

  5. Simplify further: [ y'(\text{e}) = e^1 \cdot 2 \cdot \frac{1}{\text{e}} = 2 ]

So, ( y'(\text{e}) = 2 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7